(untitled) - Schmidt, Lanny D. (New York, 1998)
Today and in future chemical engineers must be able to use their knowledge of reactors in combination with other skills in order to think creatively and strategically about new processes and growing applications. The book addresses these issues by focusing on the analysis of chemical reactors while simultaneously providing a description of industrial chemical processes and strategies by which they operate.
Keywords: Chemical reactors